A shared heritage, the growth of civilizations in India and Iran - Indian History Congress. Session 2001 : Bhopal, India); Habib, Irfan; Aligarh Historians Society (New Delhi : Tulika, 2002)
Contributed articles presented at the 62nd session of Indian History Congress, Bhopal on 29-30 December 2001.
"Aligarh Historians Society."
Includes bibliographical references and index.
Keywords: India -- Civilization -- Iranian influences -- Congresses; Iran -- Civilization -- Indic influences -- Congresses